2016
DOI: 10.1002/ajpa.22931
|View full text |Cite
|
Sign up to set email alerts
|

Does the primate pattern hold up? Testing the functional significance of infraorbital foramen size variation among marsupials

Abstract: Results suggest that relatively small IOF area may reflect increased reliance on the hands while feeding, and that relative IOF size can be used as an indicator of feeding behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The earliest known euprimates had relatively small Infraorbital foramina (IOF; Kay & Cartmill, ), which suggests that they depended less on ‘face touch’ (maxillary mechanoreception) than most other mammals. It has been suggested that reduced facial mechanorecption is functionally related to transferring touch discrimination from snout to fingers (Muchlinski, , ; Spriggs, Muchlinski, & Gordon, ), which would be important in visual predation when using the hands to capture prey.…”
Section: Evaluation Of Primate Origins Scenariosmentioning
confidence: 99%
“…The earliest known euprimates had relatively small Infraorbital foramina (IOF; Kay & Cartmill, ), which suggests that they depended less on ‘face touch’ (maxillary mechanoreception) than most other mammals. It has been suggested that reduced facial mechanorecption is functionally related to transferring touch discrimination from snout to fingers (Muchlinski, , ; Spriggs, Muchlinski, & Gordon, ), which would be important in visual predation when using the hands to capture prey.…”
Section: Evaluation Of Primate Origins Scenariosmentioning
confidence: 99%